The challenges of the ageing for the old age social protection. Reflecting from Latin America - T. Minoldo, María Sol; Peláez, Enrique (Papeles de Población, 2018)
Adequate and rigorous methodological tools to describe, quantify and understand ageing population is essential for knowing its challenges and being able to recommend relevant policies. That is why we propose to evaluate the rigor and robustness of the evidence with which we analyse the material impact of the age structure transformation, critically reviewing the indicator of demographic dependence (counterpart of the support ratio) and, especially, the economic dependence ratio. Next, we try to contribute to the design of suitable instruments to empirically address the problem of study. The work of analysis is based on the case of six countries, which are the six Latin American countries already present in the base of National Transfer Account (NTA): Argentina, Uruguay, Chile, Brazil, Mexico and Costa Rica.